Preparation method of modified waste concrete recycled aggregate and artificial stone prepared from modified waste concrete recycled aggregate

By crushing, oscillating water washing, immersing of modified solution and coating of phenolic resin, the problems of low strength and high water absorption of waste concrete are solved, and the mechanical properties of artificial stone are significantly improved and Resource utilization rate.

CN119461927AActive Publication Date: 2025-02-18CHINA STATE CONSTR HAILONG TECH CO LTD +1

Patent Information

Application Number
CN202411662840.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the prior art, the strength of waste cement concrete recycled aggregate is low, the surface hardened cement mortar has many edges and angles, high water absorption, and is not easy to bond, which limits its application.

Method used

By crushing and sieving the waste cement concrete recycled aggregate, oscillating water washing, immersion of modified solution, phenolic resin coating, etc., the edges and angles are reduced, the strength is improved, the water absorption is reduced, and the adhesion is improved.

Benefits of technology

It significantly improves the mechanical properties of artificial stone, reduces porosity and water absorption, enhances the structural integrity and compactness of aggregates, and realizes efficient resource utilization of waste concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143881940000091
    Figure BDA0005143881940000091
  • Figure BDA0005143881940000101
    Figure BDA0005143881940000101
Patent Text Reader

Abstract

The invention relates to a preparation method of a modified waste concrete recycled aggregate, which comprises the following steps: crushing waste concrete, screening the crushed waste concrete with a proper particle size to serve as a raw material of the recycled aggregate, washing with a shaking sieve to remove part of edges and corners about to fall off, and carrying out gelation reaction by using modified solutions such as nano silicon dioxide and water-soluble silicate to obtain the modified waste concrete recycled aggregate. According to the invention, fine pores on the surfaces of concrete particles are blocked and repaired, so that the structure is complete and compact, the mechanical strength of the aggregate is enhanced, the porosity and the water absorption rate are reduced, and the water absorption and the mechanical strength are further reduced through phenolic resin coating. The modified waste concrete recycled aggregate is mixed with cement, zeolite powder and the like, the mixture is pressed into a blank, and the artificial stone with excellent mechanical properties and low water absorption is obtained after carbonization curing. The method provided by the invention has good application prospects and environmental protection significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a method for preparing modified waste concrete recycled aggregate and artificial stone prepared therefrom. Background Art

[0002] In the process of development of the construction industry, construction solid waste will inevitably be generated. The accumulation of industrial solid waste not only leads to serious environmental problems, but also causes waste of resources and affects sustainable development. Waste cement concrete is one of the construction solid wastes, and accounts for a large proportion. Most of the existing treatment methods are to collect them in a centralized manner for backfill treatment, and the utilization value is not high. Waste cement concrete after crushing and screening can be used as recycled aggregate, and a large amount of micropowder can also be directly used as a raw material for cement. Therefore, using waste cement concrete as recycled aggregate to replace natural aggregate to prepare artificial stone is an effective measure to solve the storage of construction solid waste and reduce pollution.

[0003] The recycled aggregate obtained after crushing and screening of waste cement concrete has low strength, hardened cement mortar attached to its surface, with many edges and corners, high water absorption and difficulty in bonding. The damage to the waste cement concrete during the crushing process causes microcracks inside it, which has low strength and obvious disadvantages compared with natural aggregates, greatly limiting its application. With the increase in carbon dioxide emissions, the composition of the atmosphere has gradually changed, and the air quality has been greatly affected, which not only affects the ecological environment, but also endangers human health. If CO2 is used to cure artificial stone prepared from waste cement concrete, CO2 is used to react with the body to generate CaCO3. Compared with natural curing and other curing methods, carbonization curing can improve the strength of artificial stone and achieve efficient carbon fixation.

[0004] There are precedents for studying artificial stone in China, such as Chinese patent CN 112897956A "Environmentally friendly inorganic artificial stone and its preparation method", which uses copper tailings and waste concrete to replace quartz sand 100%. The limitation is that it first performs steam curing and then natural curing, and the curing cycle is long. Chinese patent CN 107540322A "Inorganic artificial stone containing high-performance ceramsite and superabsorbent resin and its preparation method" uses microwave carbonization curing to cure artificial stone, so that the surface density of the product is improved. The limitation is that it uses natural aggregates and does not realize the resource utilization of construction solid waste. Therefore, it is necessary to develop an artificial stone with good performance and can realize the recycling of construction solid waste. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a method for preparing modified waste concrete recycled aggregate and artificial stone prepared therefrom. By processing the waste concrete recycled aggregate, the edges and corners of the waste concrete recycled aggregate can be reduced, the strength can be increased, the water absorption can be reduced, the adhesion can be improved, and the mechanical properties of the artificial stone can be greatly increased.

[0007] (II) Technical solution

[0008] In a first aspect, the present invention provides a method for preparing modified waste concrete recycled aggregate, comprising:

[0009] S1, crushing and screening the waste cement concrete to obtain waste concrete particles;

[0010] S2, placing the waste concrete particles on a vibrating screen immersed in water for vibrating washing, and drying after washing;

[0011] S3, prepare a modified solution, the modified solution is composed of 3-9 parts by mass of an additive, 5-10 parts by mass of nano-silicon dioxide, 15-25 parts by mass of a water-soluble silicate, and 50-60 parts of water; wherein the water-soluble silicate is at least one of sodium silicate, potassium silicate and lithium silicate; the additive is at least one of a penetrant, a preservative and a pH adjuster; immerse the waste concrete particles treated by S2 into the modified solution for 1-6 hours, and after taking out, place them indoors to wait for natural drying;

[0012] S4, using a high-pressure water gun to rinse the waste concrete particles treated in S3, and then drying them;

[0013] S5, preparing a phenolic resin solution containing 1-5% by mass concentration of phenolic resin, and adding a curing agent at 2-3% by mass of the phenolic resin; subjecting the dried waste concrete particles in S4 to microwave treatment for 0.5-1h, spraying the phenolic resin solution on the surface of the waste concrete particles using a spray device, and stirring the waste concrete particles during the spraying process to ensure uniform spraying; curing the phenolic resin to obtain modified waste concrete recycled aggregate.

[0014] According to a preferred embodiment of the present invention, in S1, the waste cement concrete with mesh sizes of 4-160 is retained for subsequent preparation of recycled aggregate, and the part above the 4-mesh sieve is continuously crushed; the part below the 160-mesh sieve is ground to obtain recycled concrete powder or recycled to make cement; in S2, the mesh number of the oscillating screen is 200 mesh, and the part above the sieve is retained; the mud produced from the part below the sieve is ground and dried to obtain recycled concrete powder.

[0015] According to a preferred embodiment of the present invention, in S3, the pH of the modified solution is ≥11, preferably ≥12. Under alkaline conditions, the stability and permeability of the modified solution are better. The pH can also activate the waste concrete particles, so that they can react with the modified solution and block the fine cracks of the waste concrete particles. During the impregnation process, vacuum impregnation or ultrasonic treatment can be used to improve the impregnation effect.

[0016] According to a preferred embodiment of the present invention, in S3, the penetrant is one or more of triethanolamine, polyvinyl chloride, fatty alcohol polyoxyethylene ether, etc.; the preservative is mainly a special preservative for concrete used to prevent corrosion by sulfate ions and chloride ions; and the pH adjuster is sodium hydroxide.

[0017] According to a preferred embodiment of the present invention, in S5, the curing agent in the phenolic resin solution is hexamethylenetetramine HMTA or formaldehyde; the amount of formaldehyde is 1%-2% of the mass of the phenolic resin; and the amount of HMTA is 1%-3% of the mass of the phenolic resin.

[0018] According to a preferred embodiment of the present invention, in S5, 1 g to 3 g of phenolic resin is sprayed for every 100 g of waste concrete particles.

[0019] In a second aspect, the present invention provides an environmentally friendly artificial stone, which comprises the modified waste concrete recycled aggregate prepared by any one of the above embodiments.

[0020] In a third aspect, the present invention provides a method for preparing an environmentally friendly artificial stone, comprising:

[0021] Step 1: Classify the modified waste concrete recycled aggregate prepared in any of the above embodiments according to the particle size, and divide it into first-grade recycled aggregate <0.425 mm, first-grade recycled aggregate 0.425 mm-2.36 mm, and third-grade recycled aggregate 2.36 mm-4.75 mm;

[0022] Step 2: Mix and stir according to the following formula to obtain a uniform mixture:

[0023] First-grade recycled aggregate 10-20wt%; second-grade recycled aggregate 30wt%-40wt%; third-grade recycled aggregate 12wt%-20wt%; cement 12wt%-15wt%; zeolite powder 2wt%-4wt%; recycled concrete powder (the accompanying product of the modified waste concrete recycled aggregate of the present invention) 2wt%-4wt%; metakaolin 2wt%-5wt%; water reducer 1wt%-2wt%; styrene-butadiene emulsion 2wt%-8wt%; water 2wt%-4wt%; sodium pyrophosphate 1wt%-2wt%;

[0024] Step 3: Pressing the mixture into a blank, carbonizing and curing the blank to obtain the artificial stone.

[0025] According to a preferred embodiment of the present invention, the cement is phosphate cement.

[0026] According to a preferred embodiment of the present invention, metakaolin, zeolite powder and recycled concrete powder constitute auxiliary cementitious materials; metakaolin accounts for 30wt%-70wt% of the auxiliary cementitious materials; zeolite powder accounts for 20wt%-30wt% of the auxiliary cementitious materials; recycled concrete powder accounts for 20wt%-30wt% of the auxiliary cementitious materials.

[0027] The particle size of the metakaolin is less than 10 μm, preferably less than 5 μm; the specific surface area is 4000-5000 cm 2 / g; the particle size of the zeolite powder is less than 10 μm, preferably less than 5 μm; the specific surface area is 3000-5000 cm 2 / g.

[0028] According to a preferred embodiment of the present invention, the water reducer is at least one of a polycarboxylate water reducer, a naphthalene water reducer and sodium lignin sulfonate. Sodium pyrophosphate acts as a retarder in the mixture, and styrene-butadiene emulsion is an organic binder (a commercially available product, usually with a solid content of about 50%), which improves the temperature resistance and toughness of the artificial stone.

[0029] According to a preferred embodiment of the present invention, in step 3, the method for pressing the blank is as follows: the mixed material is placed in an oscillating mold frame, and a blank is obtained by static pressing, and the static pressing pressure is 1.5×10 5 N-2×10 5 N, the pressing time is 20s-40s.

[0030] According to a preferred embodiment of the present invention, in step 3, the carbonization curing conditions are: curing temperature of 10°C-50°C, relative humidity of 20%-80%, carbon dioxide concentration of 10%-90%, curing time of 2h-24h, gas pressure of 0.05-1MPa. Carbonization curing is completed in a carbonization box.

[0031] (III) Beneficial effects

[0032] (1) When preparing the modified waste concrete recycled aggregate, the present invention first crushes and screens to remove particularly fine waste concrete powder, then vibrates and washes the waste concrete particles to further remove sharp corners and floating dust, and further reduces the edges and loose edges of the waste concrete particles through the collision between particles under the action of hydraulic power and vibrating screen, thereby improving the sphericity of the particles. After vibrating and washing, particularly fine particles are further removed, and particles with a particle size greater than 200 mesh (74 μm) are retained. After drying, permeable crystalline materials such as nano-silicon dioxide and water-soluble silicates are used to allow active nano-silicon dioxide to enter the fine pits and fine cracks on the waste concrete particles under alkaline conditions and generate CHS (calcium silicon hydrate) gel. Water-soluble silicates (such as sodium silicate) can provide additional silicate ions in an alkaline environment to promote the formation of CSH gel, thereby achieving the blocking and repair of tiny cracks on the waste concrete particles, thereby improving the structural integrity, density and strength of the waste concrete particles, reducing porosity and moisture absorption rate, and improving the sphericity of the waste concrete particles. In order to improve the impregnation and penetration effect, ultrasonic vibration can be used to assist the impregnation. Then, a high-pressure water gun is used to wash away the unreacted modified solution components and floating ash, and then the waste concrete recycled aggregate is obtained by coating with phenolic resin. The coating process further improves the strength of the recycled aggregate and reduces its high water absorption rate, so that the prepared recycled aggregate has a wider application prospect, completely replacing or partially replacing natural quartz sand, reducing the mining of natural aggregates, and has economic benefits and environmental significance.

[0033] (2) In the environmentally friendly artificial stone prepared by the present invention, the waste concrete recycled aggregate replaces natural quartz sand, and the replacement rate reaches 100%, which saves the amount of cement, avoids the mining of natural stones, alleviates the storage and land occupation problems of construction solid waste, realizes the resource utilization of solid waste, reduces the manufacturing cost of artificial stone, and reduces the dependence and mining of artificial stone on non-renewable natural materials.

[0034] (3) The preparation process of the artificial stone of the present invention rationally utilizes the recycled aggregate (and recycled concrete powder) of waste concrete to recycle the waste concrete. At the same time, the curing method of the present invention is carbonization curing, which has a short curing time, achieves carbon fixation and reduces carbon emissions, and has good environmental protection significance.

[0035] (4) The method for preparing artificial stone of the present invention can obtain artificial stone with high strength and excellent performance. The styrene-butadiene emulsion added to the artificial stone and the recycled aggregate coated with phenolic resin film can form a good bond, which is beneficial to improving the fracture toughness of the artificial stone.

[0036] In summary, the present invention has the advantages of energy saving and environmental protection, carbon reduction and carbon fixation, high economic benefit and low cost, and has good application prospects. DETAILED DESCRIPTION

[0037] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific embodiments. The phenolic resins used in the following embodiments and comparative examples are the same, that is, the same commercially available product.

[0038] Example 1

[0039] This embodiment provides a method for preparing modified waste concrete recycled aggregate, which comprises:

[0040] (1) The waste cement concrete is crushed and screened to obtain waste concrete particles. The waste concrete is initially screened after being crushed, and the initial screening is respectively passed through a 4-mesh sieve and a 160-mesh sieve. After passing through the 4-mesh sieve, the undersize portion is retained, and the oversize portion of the 4-mesh sieve is further crushed. The oversize portion of the 160-mesh sieve is retained and used to prepare modified waste concrete recycled aggregate, while the undersize portion of the 160-mesh sieve is too fine and is further ground to be used as recycled concrete powder RCP. The recycled concrete powder RCP can be used to make artificial stone, or it can be recycled and used to produce new cement.

[0041] (2) The retained waste concrete particles are placed in an electric vibrating screen, which is immersed in water, and the waste concrete particles are vibrated and washed. Each batch of waste concrete particles is vibrated and washed for 2 hours. The mesh size of the vibrating screen is 200 meshes, and the part on the screen is retained and dried; the mud produced in the part under the screen is ground and dried to obtain recycled concrete powder.

[0042] (3) preparing a modified solution; the modified solution is composed of 1 part by mass of a penetrant triethanolamine, 1 part by mass of a special concrete preservative, 2 parts by mass of a pH adjuster, 6 parts by mass of nano-silicon dioxide, 12 parts by mass of lithium silicate, 12 parts by mass of sodium silicate, and 56 parts by mass of deionized water. The pH of the modified solution is 11.3.

[0043] (4) After drying the portion above the sieve retained in step (2), immerse it in the above-mentioned modified solution, soak it for 3 hours, take it out, place it indoors overnight, and wait for natural drying.

[0044] (5) Using a high-pressure water gun to rinse the waste concrete particles treated in step (4), and then drying them.

[0045] (6) Prepare a 2% phenolic resin solution, add 2% hexamethylenetetramine HMTA as a curing agent based on the dry weight of the phenolic resin, stir evenly and set aside.

[0046] (7) The waste concrete particles are treated with microwaves for 40 minutes to further dry the water contained therein, and then sprayed onto the surface of the waste concrete particles using a spray gun, with 100g of phenolic resin solution (containing 2g of phenolic resin) corresponding to 100g of waste concrete particles. During the spraying process, the waste concrete particles are turned over to ensure uniform spraying. When the phenolic resin is solidified, the modified waste concrete recycled aggregate is obtained.

[0047] Example 2

[0048] This embodiment is the same as embodiment 1, except that the composition of the modified solution in step (3) is different. In this embodiment, the modified solution is composed of 1 mass part of penetrant triethanolamine, 3 mass parts of pH regulator, 5 mass parts of nano-silicon dioxide, 10 mass parts of lithium silicate, 10 mass parts of potassium silicate, and 50 mass parts of deionized water. The pH of the modified solution is 12.4.

[0049] Then, the sieve portion retained in step (2) is dried and immersed in the above-mentioned modified solution, and ultrasonic assisted penetration is performed during the immersion process. After immersion for 1 hour, it is taken out and placed indoors overnight to wait for natural drying. The remaining steps are all referred to Example 1, thereby obtaining modified waste concrete recycled aggregate.

[0050] Example 3

[0051] This embodiment is the same as embodiment 1, except that the composition of the modified solution in step (3) is different. In this embodiment, the modified solution is composed of 1 mass part of a special concrete preservative, 2 mass parts of a pH regulator, 10 mass parts of nano-silicon dioxide, 8 mass parts of lithium silicate, 5 mass parts of potassium silicate, and 60 mass parts of deionized water. The pH of the modified solution is 11.1.

[0052] Then, the sieve portion retained in step (2) is dried and immersed in the above-mentioned modified solution. During the soaking process, the sieve portion is soaked under vacuum conditions for 1.5 hours, then taken out and placed indoors overnight to wait for natural drying. The remaining steps are all referred to Example 1, thereby obtaining modified waste concrete recycled aggregate.

[0053] Comparative Example 1

[0054] In this comparative example, the waste concrete particles that have been shaken and washed with water are subjected to the phenolic resin coating treatment of steps (6)-(7) in Example 1 without the treatment of steps (3)-(5), and modified waste concrete recycled aggregate is obtained.

[0055] Example 4

[0056] In this embodiment, the modified waste concrete recycled aggregate prepared in Example 1 is used to prepare artificial stone, and the preparation method is as follows:

[0057] (1) The modified waste concrete recycled aggregate prepared in Example 1 was classified according to the particle size into first-grade recycled aggregate of less than 0.425 mm, first-grade recycled aggregate of 0.425 mm-2.36 mm, and third-grade recycled aggregate of 2.36 mm-4.75 mm.

[0058] (2) Mix and stir according to the following formula to obtain a uniform mixture.

[0059] 14wt% of first-grade recycled aggregate; 35wt% of second-grade recycled aggregate; 19wt% of third-grade recycled aggregate; 13wt% of phosphate cement; 3wt% of zeolite powder; 3wt% of recycled concrete powder; 3wt% of metakaolin; 1wt% of polycarboxylic acid water reducer; 6wt% of styrene-butadiene emulsion (solid content is 50%); 2wt% of water; 1wt% of sodium pyrophosphate, a total of 100wt%. The mass ratio of metakaolin, zeolite powder and recycled concrete powder is 1:1:1. The specific surface area of ​​metakaolin and zeolite powder is 4000-5000cm 2 / g.

[0060] (3) The mixed material is placed in an oscillating mold frame and statically pressed to obtain a green body. The static pressing pressure is 1.6×10 5 N, press for 40s to obtain a green body, and place the green body in a carbonization box for curing. The temperature of the carbonization box is 30°C, the relative humidity is 50%, the air pressure is 0.05MPa, the carbon dioxide concentration is 60%, and the curing is for 12h.

[0061] Example 5

[0062] In this embodiment, the modified waste concrete recycled aggregate prepared in Example 2 is used to prepare artificial stone according to steps (1)-(2) of Example 4, and step (3) is changed to: the mixed material is placed in an oscillating mold frame, and a green body is obtained by static pressing. The static pressing pressure is 1.5×10 5 N, press for 40s to obtain a green body, and place the green body in a carbonization box for curing at a temperature of 50°C, a relative humidity of 40%, an air pressure of 0.08MPa, and a carbon dioxide concentration of 70% for 18h.

[0063] Example 6

[0064] In this embodiment, the modified waste concrete recycled aggregate prepared in Example 3 was used to prepare artificial stone according to steps (1)-(2) of Example 4, and step (3) was changed to: the mixture was placed in an oscillating mold frame and statically pressed to obtain a green body. The static pressing pressure was 2.0×10 5 N, press for 20s to obtain a green body, and place the green body in a carbonization box for curing at a temperature of 40°C, a relative humidity of 30%, an air pressure of 0.1MPa, and a carbon dioxide concentration of 60% for 24h.

[0065] Example 7

[0066] This embodiment uses the modified waste concrete recycled aggregate prepared in Example 1 to prepare artificial stone. The only difference between this embodiment and Example 4 is the different proportion of the mixture. The mixture composition in this embodiment is as follows: 14wt% of first-level recycled aggregate; 35wt% of second-level recycled aggregate; 19wt% of third-level recycled aggregate; 13wt% of phosphate cement; 2.7wt% of zeolite powder; 1.8wt% of recycled concrete powder; 4.5wt% of metakaolin; 1wt% of polycarboxylic acid water reducer; 6wt% of styrene-butadiene emulsion (solid content is 50%); 2wt% of water; 1wt% of sodium pyrophosphate, a total of 100wt%. The mass ratio of metakaolin, zeolite powder and recycled concrete powder is 5:3:2. The specific surface area of ​​metakaolin and zeolite powder is 4000-5000cm 2 / g.

[0067] Comparative Example 2

[0068] In this comparative example, the modified waste concrete recycled aggregate prepared in comparative example 1 was used to prepare artificial stone according to the method of example 4.

[0069] Comparative Example 3

[0070] In this comparative example, natural river sand was used to prepare artificial stone according to the grading and method of Example 4.

[0071] Comparative Example 4

[0072] In this embodiment, the modified waste concrete recycled aggregate prepared in Example 1 is used to prepare artificial stone, except that the curing conditions are as follows: the green body is naturally cured at a curing temperature of 25° C., a humidity of 30%, and a curing period of 7 days.

[0073] The artificial stone samples prepared in Examples 4-7 and Comparative Examples 2-4 were tested for flexural strength with reference to JC / T2604-2021 "Stone-like concrete panels and tiles"; the compressive strength test was performed using a press at a rate of 2.5 kN / s until the sample was damaged; and the water absorption rate of the artificial stones obtained in Examples 4-7 and Comparative Examples 2-4 was tested with reference to GB / T4111-2013 "Test methods for concrete blocks and bricks". The test results are shown in Table 1.

[0074] Table 1: Compressive strength, flexural strength and water absorption of artificial stone in each preparation example

[0075]

[0076]

[0077] From the test results in Table 1, it can be concluded that the compressive strength and flexural strength of the artificial stones prepared in Examples 4-7 are higher than those in Comparative Example 2 and Comparative Example 4; compared with the artificial stones made of natural quartz sand in Comparative Example 3, the compressive strength, flexural strength, water absorption rate, etc. of the artificial stones prepared in Examples 4-7 of the present invention are basically equivalent or even slightly better. Among them, Example 7 further adjusts the mass ratio of metakaolin, zeolite powder, and recycled concrete powder in the mixture, so that the mechanical properties of the artificial stone are the best in each embodiment. The recycled aggregate used in Comparative Example 2 is waste concrete particles that have not been treated with a modified solution. Although the waste concrete particles are coated with phenolic resin, the mechanical strength of the artificial stone finally prepared is still poor and the water absorption rate is also high. The composition of the artificial stone in Comparative Example 4 is the same as that in Example 1, but it is cured under natural curing conditions. Not only is the curing period longer, but the mechanical properties of the artificial stone finally prepared are also inferior to those of Example 4.

[0078] The present invention uses waste concrete as recycled aggregate, washes it with water through an oscillating screen, removes some edges and corners that are about to fall off, uses nano-silicon dioxide, water-soluble silicate, etc. to perform gelation reaction, blocks and repairs the micropores on the surface of waste concrete particles, makes its structure complete and compact, enhances the mechanical strength of the aggregate, reduces porosity and water absorption, and then coats it with phenolic resin to further reduce water absorption. The carbonization curing method of artificial stone not only gives the artificial stone higher mechanical strength, but also achieves the goal of carbon reduction and carbon fixation. Therefore, the method of the present invention has good application prospects and environmental significance.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing modified waste concrete recycled aggregate, characterized in that: include: S1, crushing and screening the waste cement concrete to obtain waste concrete particles; S2, placing the waste concrete particles on a vibrating screen immersed in water for vibrating washing, and drying after washing; S3, prepare a modified solution, the modified solution is composed of 3-9 parts by mass of an additive, 5-10 parts by mass of nano-silicon dioxide, 15-25 parts by mass of a water-soluble silicate, and 50-60 parts of water; wherein the water-soluble silicate is at least one of sodium silicate, potassium silicate and lithium silicate; the additive is at least one of a penetrant, a preservative and a pH adjuster; immerse the waste concrete particles treated by S2 into the modified solution for 1-6 hours, and after taking out, place them indoors to wait for natural drying; S4, using a high-pressure water gun to rinse the waste concrete particles treated in S3, and then drying them; S5, preparing a phenolic resin solution containing 1-5% by mass concentration of phenolic resin, and adding a curing agent at 2-3% by mass of the phenolic resin; subjecting the dried waste concrete particles in S4 to microwave treatment for 0.5-1h, spraying the phenolic resin solution on the surface of the waste concrete particles using a spray device, and stirring the waste concrete particles during the spraying process to ensure uniform spraying; after the phenolic resin is cured, a modified waste concrete recycled aggregate is obtained.

2. The preparation method according to claim 1, characterized in that: In S1, when crushing and screening, the waste cement concrete with 4-160 mesh is retained for the subsequent preparation of recycled aggregate, and the part above the 4-mesh sieve is further crushed; the part below the 160-mesh sieve is ground to obtain recycled concrete powder or recycled to make cement; in S2, the mesh number of the oscillating screen is 200 mesh, and the part above the sieve is retained; the mud produced in the part below the sieve is ground and dried to obtain recycled concrete powder.

3. The preparation method according to claim 1, characterized in that: In S3, the pH of the modified solution is ≥11.

4. The preparation method according to claim 1, characterized in that: In S3, the penetrant is one or more of triethanolamine, polyvinyl chloride, fatty alcohol polyoxyethylene ether, etc.; the preservative is mainly a special preservative for concrete used to prevent corrosion by sulfate ions and chloride ions; and the pH adjuster is sodium hydroxide.

5. The preparation method according to claim 1, characterized in that: In S5, the curing agent in the phenolic resin solution is hexamethylenetetramine HMTA or formaldehyde; the amount of formaldehyde used is 1%-2% of the mass of the phenolic resin; and the amount of HMTA is 1%-3% of the mass of the phenolic resin.

6. The preparation method according to claim 1, characterized in that: In S5, 1 g to 3 g of phenolic resin is sprayed per 100 g of waste concrete particles.

7. A method for preparing an environmentally friendly artificial stone, characterized in that: It includes: Step 1: Classifying the modified waste concrete recycled aggregate prepared by the preparation method according to any one of claims 1 to 6 according to the particle size, and dividing it into first-grade recycled aggregate of less than 0.425 mm, first-grade recycled aggregate of 0.425 mm-2.36 mm, and third-grade recycled aggregate of 2.36 mm-4.75 mm; Step 2: Mix and stir according to the following formula to obtain a uniform mixture: First-grade recycled aggregate 10-20wt%; second-grade recycled aggregate 30wt%-40wt%; third-grade recycled aggregate 12wt%-20wt%; cement 12wt%-15wt%; zeolite powder 2wt%-4wt%; recycled concrete powder 2wt%-4wt%; metakaolin 2wt%-5wt%; water reducer 1wt%-2wt%; styrene-butadiene emulsion 2wt%-8wt%; Water 2wt%-4wt%; Sodium pyrophosphate 1wt%-2wt%; Step 3: Pressing the mixture into a blank, carbonizing and curing the blank to obtain the artificial stone.

8. The preparation method according to claim 7, characterized in that: The cement is phosphate cement; the water reducer is at least one of polycarboxylate water reducer, naphthalene water reducer and sodium lignin sulfonate.

9. The preparation method according to claim 7, characterized in that: Metakaolin, zeolite powder and recycled concrete powder constitute auxiliary cementitious materials; metakaolin accounts for 30wt%-70wt% of the auxiliary cementitious materials; zeolite powder accounts for 20wt%-30wt% of the auxiliary cementitious materials; recycled concrete powder accounts for 20wt%-30wt% of the auxiliary cementitious materials.

10. The preparation method according to claim 7, characterized in that: The method of pressing the blank is as follows: the mixed material is placed in an oscillating mold frame, and a blank is obtained by static pressing. The static pressing pressure is 1.5×10 5 N-2×10 5 N, pressing time is 20s-40s; The conditions for carbonization curing are: curing temperature of 10°C-50°C, relative humidity of 20%-80%, carbon dioxide concentration of 10%-90%, curing time of 2h-24h, and gas pressure of 0.05-1MPa.

Citation Information

Patent Citations

  • Inorganic artificial stone containing high-performance ceramsite and superabsorbent resin and preparation method of inorganic artificial stone

    CN107540322A

  • Environment-friendly inorganic artificial stone and preparation method thereof

    CN112897956A

  • Anti-seepage recycled concrete and preparation method thereof

    CN109456003A

  • Renewable concrete and preparation method thereof

    CN110436837A

  • Method for preparing large-mixing-amount low-quality mineral admixture recycled cement-based product through microwave curing

    CN110510947A

Cited By

  • Preparation process of improved recycled concrete aggregate maritime work cement-based material

    CN121225962A